Conocimiento y actitudes hacia la tuberculosis pulmonar en pobladores de la Junta Vecinal Pasaje San Lorenzo Distrito de Punchana 2024 - Quispe Panduro, Sisara Sarita (Universidad Nacional de la Amazonía Peruana, 2025)
Pulmonary tuberculosis remains a public health problem in Peru, especially in urban-marginal areas such as the district of Punchana, where significant gaps in knowledge and attitudes toward this disease persist. The objective of this study was to determine the relationship between knowledge and attitudes toward pulmonary tuberculosis among adult residents of both sexes in the Pasaje San Lorenzo Neighborhood Board of the Punchana District, 2024. The study was quantitative, with a non-experimental correlational design. The sample consisted of 81 individuals. Interviews and home visits were used. The instruments were a knowledge questionnaire on pulmonary tuberculosis (validity 96.11%; reliability 94.50%) and a Likert-type scale on attitudes toward pulmonary tuberculosis (validity 97.33%; reliability 95.70%). The results showed that 68 (84.0%) of the residents had low knowledge, while 13 (16.0%) had high knowledge. Regarding attitudes toward pulmonary tuberculosis, 61 (75.3%) showed rejection, and 20 (24.7%) showed acceptance. A statistically significant relationship was found between knowledge and attitudes toward pulmonary tuberculosis (X²c = 47, 230; p=0,001; α = 0.05). It is concluded that the residents have low knowledge and rejecting attitudes toward pulmonary tuberculosis; therefore, an immediate educational intervention is needed to reduce this current social problem.

La tuberculosis pulmonar continúa siendo un problema de salud pública en el Perú, especialmente en zonas urbano marginales como el distrito de Punchana, donde persisten brechas significativas en el conocimiento y actitud hacia esta enfermedad. El objetivo del estudio fue determinar la relación entre conocimientos y actitudes hacia la tuberculosis pulmonar en pobladores adultos de ambos sexos de la Junta Vecinal Pasaje San Lorenzo del Distrito de Punchana, 2024. El estudio fue cuantitativo, con un diseño no experimental correlacional. La muestra fue de 81 personas. Se utilizaron la entrevista y visita domiciliaria. Los instrumentos fueron un cuestionario de conocimientos sobre tuberculosis pulmonar (validez 96,11%; confiabilidad 94,50%) y una escala tipo Likert sobre actitudes hacia la tuberculosis pulmonar (validez 97,33%; confiabilidad 95,70%). Los resultados fueron: 68 (84,0%) de los pobladores tenían conocimientos bajos; 13 (16,0%), conocimientos altos. En cuanto a las actitudes hacia la tuberculosis pulmonar, 61 (75,3%) fueron de rechazo; 20 (24,7%), de aceptación. Se encontró significancia estadística entre conocimientos y actitudes hacia la tuberculosis pulmonar (X²c = 47, 230; p=0,001; α = 0.05). Se concluye que los pobladores tienen bajos conocimientos y actitudes de rechazo hacia la tuberculosis pulmonar, por lo que requieren una intervención educativa inmediata para disminuir este problema social actual.
Keywords: Tuberculosis pulmonar; Actitud; Conocimiento; https://purl.org/pe-repo/ocde/ford#3.03.03